Pregunta
upstudy study bank question image url

Evaluate the integral. \[ \int_{1}^{2} \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} d y \]

Ask by Rose Reeves. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The integral evaluates to \( \frac{4}{5} \ln\left(\frac{8}{3}\right) \).

Solución

We wish to evaluate   I = ∫ from y = 1 to 2 of (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] dy. Step 1. Write the integrand in partial fractions. Assume that   (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] = A/y + B/(y + 2) + C/(y – 3). Multiply both sides by y(y + 2)(y – 3) to clear denominators:   4y² – 2y – 12 = A(y + 2)(y – 3) + B·y(y – 3) + C·y(y + 2). Step 2. Expand and Collect Like Terms. First, expand A(y + 2)(y – 3). Notice that   (y + 2)(y – 3) = y² – y – 6, so  A(y² – y – 6) = A·y² – A·y – 6A. Next, expand B·y(y – 3):   B·y(y – 3) = B·y² – 3B·y. Then, expand C·y(y + 2):   C·y(y + 2) = C·y² + 2C·y. Now, combine all the terms:   A·y² – A·y – 6A + B·y² – 3B·y + C·y² + 2C·y = (A + B + C)y² + (–A – 3B + 2C)y – 6A. Step 3. Equate coefficients with the numerator 4y² – 2y – 12:   Coefficient of y²: A + B + C = 4,   Coefficient of y: –A – 3B + 2C = –2,   Constant term: –6A = –12. From the constant term, solve for A:   –6A = –12 ⟹ A = 2. Now substitute A = 2 into the first equation:   2 + B + C = 4 ⟹ B + C = 2.                       (1) Substitute A = 2 into the y–coefficient equation:   –2 – 3B + 2C = –2 ⟹ –3B + 2C = 0 ⟹ 2C = 3B ⟹ C = (3/2)B.      (2) Now substitute (2) into (1):   B + (3/2)B = 2 ⟹ (5/2)B = 2 ⟹ B = (2·2)/5 = 4/5. Then, from (2), C = (3/2)(4/5) = 6/5. Thus, the partial fractions are:   (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] = 2/y + (4/5)/(y + 2) + (6/5)/(y – 3). Step 4. Integrate Term by Term. The integral becomes:   I = ∫ from 1 to 2 [2/y] dy + (4/5) ∫ from 1 to 2 [1/(y + 2)] dy + (6/5) ∫ from 1 to 2 [1/(y – 3)] dy. Each integral is a standard logarithmic form: • ∫ 1/y dy = ln |y| + C, • ∫ 1/(y + 2) dy = ln |y + 2| + C, • ∫ 1/(y – 3) dy = ln |y – 3| + C. Perform the integrations:   I = 2[ln |y|]₁² + (4/5)[ln |y + 2|]₁² + (6/5)[ln |y – 3|]₁². Evaluate each piece: 1. For 2[ln |y|] from 1 to 2:   = 2 (ln 2 – ln 1) = 2 ln 2   (since ln 1 = 0). 2. For (4/5)[ln |y + 2|] from 1 to 2:   = (4/5) (ln |2 + 2| – ln |1 + 2|) = (4/5)(ln 4 – ln 3). 3. For (6/5)[ln |y – 3|] from 1 to 2:   At y = 2, y – 3 = –1 (absolute value 1) and at y = 1, y – 3 = –2 (absolute value 2). Thus,   = (6/5)(ln 1 – ln 2) = (6/5)(0 – ln 2) = –(6/5) ln 2. Step 5. Combine the results. Add the contributions:   I = 2 ln 2 + (4/5)(ln 4 – ln 3) – (6/5) ln 2. Combine the ln 2 terms:   2 ln 2 – (6/5) ln 2 = (10/5 ln 2 – 6/5 ln 2) = (4/5) ln 2. Thus,   I = (4/5) ln 2 + (4/5)(ln 4 – ln 3)     = (4/5)[ln 2 + ln 4 – ln 3]. Recall that ln 2 + ln 4 = ln (2 · 4) = ln 8. Therefore, the answer is:   I = (4/5)[ln 8 – ln 3] = (4/5) ln(8/3). Final Answer:   ∫ from 1 to 2 (4y² – 2y – 12)⁄[y(y + 2)(y – 3)] dy = (4/5) ln(8/3).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To evaluate the integral \[ \int_{1}^{2} \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} \, dy, \] we can start by performing partial fraction decomposition on the integrand. We want to express \[ \frac{4 y^{2}-2 y-12}{y(y+2)(y-3)} \] in the form \[ \frac{A}{y} + \frac{B}{y+2} + \frac{C}{y-3}. \] Multiplying through by the common denominator \(y(y+2)(y-3)\) gives us \[ 4y^2 - 2y - 12 = A(y+2)(y-3) + B(y)(y-3) + C(y)(y+2). \] Expanding each term on the right-hand side: 1. \( A(y+2)(y-3) = A(y^2 - y - 6) = Ay^2 + (2A - 3A)y - 6A = Ay^2 + (2A - 3A)y - 6A \) 2. \( B(y)(y-3) = By^2 - 3By \) 3. \( C(y)(y+2) = Cy^2 + 2Cy \) Combining all terms yields: \[ (A + B + C)y^2 + (2A - 3B + 2C)y - 6A = 4y^2 - 2y - 12. \] Now, we equate coefficients: - For \(y^2\): \(A + B + C = 4\) - For \(y\): \(2A - 3B + 2C = -2\) - Constant: \(-6A = -12\) or \(A = 2\) Plugging \(A = 2\) into the other equations gives: 1. \(2 + B + C = 4 \implies B + C = 2\) 2. \(2(2) - 3B + 2C = -2 \implies 4 - 3B + 2C = -2 \implies 2C - 3B = -6\) Now we solve the equations: From \(B + C = 2\), we can express \(C\) as \(C = 2 - B\). Substitute this into \(2C - 3B = -6\): \[ 2(2 - B) - 3B = -6 \implies 4 - 2B - 3B = -6 \implies -5B = -10 \implies B = 2. \] Thus, \(C = 2 - 2 = 0\). We have: \[ A = 2, \quad B = 2, \quad C = 0. \] Therefore, we can rewrite our integrand as: \[ \frac{4y^2 - 2y - 12}{y(y+2)(y-3)} = \frac{2}{y} + \frac{2}{y+2}. \] Now, we can rewrite the original integral: \[ \int_{1}^{2} \left( \frac{2}{y} + \frac{2}{y+2} \right) dy. \] Now we evaluate this: \[ \int_{1}^{2} \frac{2}{y} \, dy + \int_{1}^{2} \frac{2}{y+2} \, dy. \] 1. For the first integral: \[ \int \frac{2}{y} \, dy = 2 \ln |y| \Big|_{1}^{2} = 2 (\ln 2 - \ln 1) = 2 \ln 2. \] 2. For the second integral, use the substitution \(u = y + 2\): \[ \int \frac{2}{y+2} \, dy = 2 \ln |y+2| \Big|_{1}^{2} = 2 (\ln 4 - \ln 3) = 2\ln\left(\frac{4}{3}\right). \] Putting it all together gives: \[ 2 \ln 2 + 2 \ln \left(\frac{4}{3}\right) = 2 \left(\ln 2 + \ln \left(\frac{4}{3}\right)\right) = 2 \ln \left(\frac{8}{3}\right). \] Thus,

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad